Profil Penderita Keterlambatan Bicara Dengan Pemeriksaan ASSR di TOA Jala Puspa Rumkital Dr. Ramelan Surabaya Tahun 2016 - 2017 - Yoice Emilia Gunawan; Prijanti Eka Poerwantiningroem (HANG TUAH MEDICAL JOURNAL, 2019)
Abstract Background: Speech and language delay is experienced by 5-8% of preschoolers and 17% of 5-year-olds. Delay in speech can be caused by hearing loss, brain disorders (such as mental retardation, receptive and / or expressive language-specific disorders), autism or disorders of the mouth organs that make it difficult for children to pronounce words (known as articulation disorders). The procedure for delay in speech depends on the cause, and also involves cooperation between pediatricians, other related specialists, speech therapists and of course parents. Aim: to investigate the profile of patients with speech delay with Auditory Staeady State Respon (ASSR) examination at Taman Obseravsi Anak (TOA) Jala Puspa RUMKITAL DR. RAMELAN Surabaya Research methods: This research is a descriptive research. 57 medical record data are recorded, checked for completeness, analyzed in descriptive form then presented in the form of diagrams and tables. Results: The average age of people with speech delay is 2.67 years. Most patients are male. The most prenatal history experienced by people with delayed speech is Rubella infection. The most history of Christmas is hyperbilirubinemia. Most postnatal history is autism. Hearing examination using ASSR mostly shows profound hearing loss